Geriatric Care during Public Health Emergencies: Lessons Learned from Novel Corona Virus Disease (COVID-19) Pandemic. Issue 4 (18th May 2020) - Mazumder, Hoimonty; Hossain, Md Mahbub; Das, Anupom
ABSTRACT: Geriatric care in public health emergencies is a serious concern, while, high case-fatalities among older adults across the globe in COVID-19 pandemic implies lack of preparedness. Most of the countries irrespective of developing and developed one enormously struggling because of an inchoate response system ignorant of geriatric health needs. Therefore, a robust approach is highly essential that requires an integrated emergency preparedness by addressing geriatric care.